FEATURES OF LYUDMYLA STARYTSKA-CHERNYAKHIVSKA’S DRAMA WORK CONFLICT - Protsiuk, L. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analises the drama works by Lyudmyla Starytska-Chernyakhivska in aspects of conflict. The author analyses conflict, images of the work, the plot, composition and other aspects of poetics. The article proofs psihologism as a main feature of Ukrainian drama at the beginning of last century.